Study of the tribe Gastrodieae (Orchidaceae, Epidendroideae) in Sri Lanka II: Revisiting genera Didymoplexis and Gastrodia with descriptions of one new species in each and notes on the specimen C.P.3463 housed at PDA - Bandara, Champika; Atthanagoda, Anusha Gayan; Kumar, Pankaj (Phytotaxa, 2025)
Building upon our first publication, we present here the second part of the taxonomic study of the tribe Gastrodieae (Orchidaceae) in Sri Lanka. This study is based on the field data and over 15 years of expedition records. This study provides comprehensive taxonomic descriptions of related members of genera Didymoplexis and Gastrodia in Sri Lanka, including two newly described endemic species: Didymoplexis ediriweerae and Gastrodia aenigmata. We examined each of the 16 plants on the specimen C.P.3463 at PDA, including the one taken by Schlechter and accurately determine their true identity. Additionally, we present the current status and neotypification of Gastrodia zeylanica. Detailed habitat and ecological information, conservation assessments, taxonomic notes, photographic plates, and line drawings are included for all species. Furthermore, we provide a distribution map for the members of Didymoplexis and Gastrodia in Sri Lanka, along with a field identification keys for both genera.